Simulation on centrifugal fans operating at close distance: An investigation of different air handling unit constructions to improve fan efficiency - Milikic, Filip (My University, 2021)
To ensure a proper indoor climate, ventilation is of great importance, especially for health reasons. Finding an high energy efficient ventilation unit solution is of big interest for Swegon, the company which initiated this thesis, as it copes with current EU regulations and directives for environmental issues, and at the same time lowers the operating costs. The goal with this study is to run CFD simulations on the current air handling unit, compare the results to three different modifications of the design and determine the potential improvement of the unit in terms of fan efficiency. The CFD simulations are performed with STAR-CCM+ and experimental tests are performed by Swegon, which are compared to the numerical results. A verification and validation study is performed to ensure mesh independence and realistic results. The results are compared for three different operating points for both methods, with flow rates ranging between 0.90 and 1.26 m3/s. Simulation results show that by adding a vertical wall in between the fans, which separates the flows of the fans, the potential increase of the fan efficiency for lower flow rates is up to around 2 %. For larger flow rates the increase is slightly less at around 1.5 %, however still a significant improvement from the current design. In comparison, the experiment results show efficiencies lower for the wall at around 0.5 %. The main conclusion draw from this study, which is based on both methods, is that the curved wall design shows best potential for energy efficiency, followed by the straight wall and tilted wall, and lastly by the current design.
Keywords: fan efficiency; CFD; air handling unit; centrifugal fan; ventilation; parallel operation